O dispositivo da Web: um estudo sobre a lógica do filtro de busca do Google - Arruda, Renê Eduardo (2019)
In the context of research in communication and culture creation processes, specifically in the information network culture universe, the present work aims to study the complexities that permeate the communicational phenomenon of the interactions between users of cyberspace and search results from search engines. Search engines index content from the web, organizing it according to its own logic to compose search results pages. These systems were developed to consider a series of criteria when a user inserts a query, such as keywords, user’s search history, geographic location, among others. Thus, the search results page is, to some extent, different for each user. Since 2009 Google is the most accessed search engine in the world, processing a vast amount of information. The present dissertation intends to understand the logic of the Google search results filter, mapping how the search results are personalized for each user. Due to the vastness of the web, search engines like Google have become structuring tools for user interaction in the digital informational space, determining what is displayed as a search result. Following the logic defined by its filters, Google establishes power relations, acting as an apparatus, as it modulates the search results according to the profile of each user, and also according to the social context in which it is inserted. The research method consists, first of all, in the analysis of the Google search filter from the theoretical perspectives of Foucault, Deleuze and Guattari, Lazzarato and Halavais. In parallel, an experiment was carried out to empirically verify the operation of the search filter. The experiment consists of a qualitative analysis of the search results of 5 user profiles created by the author, in order to identify differences in search results for the same search queries. The research resulted in the conceptualization of the Google search filter logic, verification of the hypothesis of divergence of search results according to each user's characteristics, and revealed evidence of the subjectivation operated by the device